Big Anthony : his story - De Paola, Tomie (New York : Puffin, 2001)
Big Anthony, well-meaning but inattentive, journeys around Italy causing one problem after another, before meeting Strega Nona.
Wilson's Children
School Library Journal
Pub Weekly
6.6
K-3
Keywords: Attention -- Fiction; Italy -- Fiction; Attention -- Fiction; Italy -- Fiction